Pengaruh Pajak Daerah Dan Retribusi Terhadap Pendapatan Asli Daerah (PAD) Dan Pendapatan Daerah Kota Kediri - Naning Fatmawatie (Realita: Jurnal Penelitian dan Kebudayaan Islam, 2015)
Local revenue of local government is a right that is recognized as an addition to net asset value during a givenÂ period. For that all goods and services as a result of economic activities that operate in the domestic territory,Â regardless of whether the factors of production derived from or owned by a resident of the area, is the GrossÂ Domestic Product. Local revenue is the revenue from the tax sector, retribution, the results of companiesÂ belonging to the region, the results of the wealth management separated areas, and other areas of legitimateÂ revenue. In Law No. 33 of 2004 on Financial Balance between Central and Local Government, it is stated that theÂ local revenue sources consist of regional revenue, Tax Revenue and Non-Tax.Â Under Law No. 34 of 2000 on the amendment of Law No. 18 of 1997 on local taxes and levies, what is meant byÂ local taxes are compulsory contributions made by individuals and entities to the area without a direct rewardÂ balance, which can be imposed by legislation in force, which is used to finance the implementation of localÂ government and regional development. Whereas levies are payment for certain services or granting specialÂ permits provided by the local government or for the benefit of private persons or entities.Â Local taxes and levies are one source of revenue (PAD). Local Revenue is one source of local revenue. The increasedÂ local taxes and levies are expected to increase revenue of an area, and the increased revenue is expected toÂ increase in local revenue.